Mindware: Critical Thinking in Everyday Life - John Eigenauer (Journal of Intelligence, 2024)
Humans make many decisions in everyday life, some of which require careful use of evidence. Because emotional and heuristic mental processes dominate human cognition, it is common to suggest that there is little hope that critical thinking tools will be widely used. However, the concept of “mindware” gives hope to the idea that critical thinking skills may be more widely deployed than they currently are. This article reflects on some impediments to critical thinking, assesses some future challenges to critical thinking being more widely used, and suggests that “mindware” modules can be used widely both in and out of educational settings to significantly enhance critical thinking in everyday life.